Analisis Putusan Mahkamah Konstitusi Nomor 68/PUU-XII/2014 tentang Perkawinan Beda Agama dalam Perspektif Hak Asasi Manusia - Syofyan, Yunita (UNES Law Review, 2023)
The validity of marriage in Indonesia is considered to have religious overtones, religious elements that dominate the requirements for a valid marriage, so there is a degradation of the achievement of the unification goal of the Marriage Law which refers to the uniformity of holding marriages for every citizen. Pluralism in Indonesia with its diversity of ethnicities and nations is not actually an obstacle for a woman and a man in Indonesia to get married. The vulnerability to interfaith marriages is quite high due to the large number of religious diversity that is recognized by the constitution but interfaith marriages are marriages that are prohibited and not recognized by the Marriage Law in Indonesia. In the perspective of Human Rights (HAM) religious marriage is not prohibited and freedom is given to brides and grooms of different religions to be able to carry out the marriage (non-derogable rights). This research is a legal research (doctrinal research) with a conceptual approach (conceptual approach), the legal approach (statues approach), and the case approach (cases approach). The results of this study explain first, the Court, in the life of the nation and state based on Pancasila and the 1945 Constitution, religion is the basis and the state has an interest in matters of marriage, it cannot only be seen from a purely formal aspect, but must also be seen from a spiritual and social aspect. Religion determines the validity of marriage. Second, interfaith marriage is part of the universal right that every individual has to carry out marriages to brides of different religions and marriage is part of a right that cannot be limited and reduced by differences in religion.